The reign of James III: the Hume Brown Prize in Scottish History, 1935 - MacRae, Christopher (The University of Edinburgh, 1935)
As the individual man passes through several well defined phases common to his kind, so does man in the group -unit, the social organism, the national entity, similarly pass through certain broad phases common, in general, to all similar group - units. As an individual person is apt to be infected by an illness which is raging among his fellows, or to be inspired by their example to emulate their achievements, so do national movements and commotions affect other nations. History goes to bear out these facts. We have had great movements - the Conversion, the Renaissance, the Reformation - which affected all nations, as the comity of nations,( or in some cases one should say "proto- nations" ),then stood. It is true that different nations, like different men, reacted differently to the same broad movement, and thereby hangs much of the interpretation of history and of life. Similarly most nations have passed through such phases as that of feudalism; they have had ages of monarchy and ages of what might be called anti - monarchy. The history of one nation can only be understood in the light of that of others.

The fifteenth century in Western Europe was a period of commotion,and, in many ways, of decline. The power of monarchy was on the wane in these years. In England the disorders of the reign of Richard ii. had been followed by the "Lancastrian ixperiment" of a kingship that had perforce to abandon the dearest right of indefeasible kingship, direct hereditary succession. By the middle of the century the Lancastrian monarchy had lost even its personal vigour, and in the long and troubled reign of the weak Henry V1 monarchy in England reached a low ebb. In France, distracted by foreign war and civil strife, monarchy reached its nadir in the anarchy of what is called "the reign "of Charles V1. In the Germany of Frederick 111, in the anarchic Spanish kingdoms of the later Middle Ages, the same tale is repeated. Everywhere medieval institutions were decaying; feudalism had entered upon a vicious old age; disorder, rapacity, violence, bloodshed and misery were rife. Yet the decadent fifteenth century was nearer to the modern age than the brilliant thirteenth. The first streaks of the Renaissance were beginning to appear and at the end of the century the lustrous light of that great dawn shone clearly forth. The suffering England of the Wars of the Roses became the England of the strong Tudor kings. In France the recovery that began under Charles V11 was continued by Louis X1 and his successors, and the new monarchy was securely established. In Spain a new age was beginning with the marriage and succession of the reforming Isabella and Ferdinand. Even the nerveless Emperor Frederick 111 laid the foundations of Hapsburg greatness by his politic marriages and eventual succession treaties. In every sphere, in art, literature, science, exploration, commerce, war, the new quickening impulse was apparent. But the Renaissance was a process that only gradually unfolded itself. Its first elements began faintly to appear long before anyone could foretell what the momentous result was to be and at first they only added another disturbing factor to the general disruption and turmoil of latter day medievalism. One remedy after another, consciously or unconsciously, was proposed until at last the growing disorder culminated in such orgies of riot and bloodshed as the struggle of Burgundian and Armagnac in France or the War of the Roses in England. From the worst horrors of protracted civil war.. Scotland was sufficiently fortunate to escape, but it too had its disorders, its bastard feudalism, its anti - monarchialism, its pre -natal pangs of the coming Renaissance. It is in the light of these considerations that the reign of James 111 may best be understood.

The older historians used to depict James 111 as wicked, weak and incapable, obstinate, frivolous, perverse, inept and unworthy; endowed with no kingly instincts, setting the narrow interests of himself and his favourites before those of his country and sinking in the end under a deserved retribution. Others have seen in him a Renaissance king of the type of Louis X1 - able, enlightened, calculating, far -seeing and shrewd, a patron of learning and the arts and a disciple of the Renaissance, misunderstood and maltreated by his rude nobles. Probably neither View is correct - as indeed extremes seldom are. He was perhaps the weakest of the Jameses but the reason for his difficulties are to be sought at least as much in the situation he came into as in his own defects of character . He was not so much a Renaissance king as a Pre -Renaissance one. The old order was failing, the first shafts of a new dawn were beginning to appear. The new was quickening in the womb of the old causing confusion and uproar in the midst of which James 111 was called upon to rule and by which in the end he was overborne. In this his reign may be compared with that of Richard 11 . Both kings were brought face to face with the evils of latter day feudalism, accentuated by a long minority. Both sought, consciously or unconsciously,to oppose it, or at the very least to escape from it. Both sought to abstract themselves from the rough tumults of their age and in so doing they began to set over against the decadent feudalism of their era something new, something that was in essence a strengthening of the royal power. For the favourites of James 111 were essentially the rudiments of a Curialist party, just as were the Veres and Suffolks or the Counter Appellants of Richard 11. On the other hand the nobles were marshalling the forces of resistance. Feudalism sensed probably, rather than understood, the beginnings of its death grips with the things of the future. Already James 1 and 11 had done much to strengthen the power of the crown against the nobles. Specially significant of the drift of things were the statutes levelled by James 11 towards the end of his reign against over -grown feudalism; the fall of the Douglases was at once an opportunity for the king and a warning to the nobility; feudalism was on its mettle and consequently baronial opposition to monarchy supplies the key -note to the troubled reign that f owed. In opposing both James and Richard the nobles might s e on the accidents of time and place as justification. Th ight say they were opposing tyranny or ineptitude, addiction to witchcraft or a base subservience to worthless favourites. They might even believe within themselves that this was all they opposed, but in reality the struggle went far deeper - it was the issue between two incompatible forces. In both reigns and probably in both kings we see the beginning of Renaissance elements striving to appear, the first shivering beams of the dawn of the modern era glimmering fitfully through the still thick impenetrable night of medievalism. The Renaissance had not yet come but its harbingers, its advance guard, so to speak, were there. The result was disjunction, confusion and uproar, in the midst of which both kings fell, martyrs in a sense, perhaps unwilling and unconscious martyrs, to the coming awakening which was to find its political ideal and salvation in the strengthening of monarchy and its independence -the consummation that they tried ineffectually to achieve. They fell partly owing to their own defects, partly to those of their countries and age, partly owing to the developing struggle between the old and the new.

The drift modernwards can be seen in many aspects of the reign of James 111. The nation was coming more fully to realise itself, to stand more self sufficiently as an entity among similar determinate entities. The organic and harmonically microcosmic system of corporation within corporation, which had been the ideal plan of the Middle Ages, theoretic universal empire with organic co- ordinated units within it and practical local independence, was being gradually displaced by the growing scheme of self sufficient rigidly delimited nations, different in kind and superior to all other group -units within it, independent of any without it. Scotland was coming to stand more securely as a nation among nations. Within herself she had attained some sort of corporate entity - nobles no longer fought in isolation for their own independence but in cliques in order to capture the government. Externally Scotland came to stand more clearly in the light of the diplomatic stage. She became more definitely a nation of Europe with a place in its politics, though as yet only the faint beginnings of this tendency were apparent.

The parliamentary act of 1469 against imperial notaries in Scotland,since the king had "jurisdiction and free empire within his realm" may be taken as significant of one aspect or result of the growing national consciousness; a more important one is evidenced by the attitude assumed towards the Holy See. The Scottish rulers in their dealings with Rome began to assume more of the character of sovereigns of an independent secular state. They might and did still seek to be regarded as obedient sons of the church but they also remembered that they were kings in their own domain, and at times these two ideals of conduct might be found to clash. This developing new spirit may be traced in the ecclesiastical dealings of the age, whether in bold statues against "barratry ", appeal and extortion, or in the circumstances of the unbeatified collusions arranged between the secular powers that were and the spiritual leaders of the universal church for the distribution of patronage and emolument.

As often is the case in an age of apparent reaction and turmoil, the reign of James 111 was marked by considerable administrative advance. In the judicial machinery, in the administration, in the keeping of records, there was considerable development - development that in many cases supplied the significant link between the Scotland that had been and the Scotland that was to be. In literature toothere was evidence of the coming revival that was to blossom forth in ensuing reigns as the Scottish Renaissance.

Altogether it was a significant reign. It is unfortunate that the scarcity of materials makes it easier to raise questions about it than to answer them. In it can be traced the working of many of the underlying forces that go to the making of history; it can well be compared with other reigns in other places, and it takes its own definite position in the sequence of Scotland's development. Many of the problems it presents must remain forever unanswered but in the attention they demand, the analogies they suggest, the attempted explanations they elicit, they shall surely, even if they be insoluble, not be deemed barren and fruitless.